Academic Senate Minutes 2012-11-08- - Academic Senate:::::::::
Approval of Agenda. Minutes postponed. Resolution Commemorating the 30th Anniversary of the SSU Vietnam Veterans' Memorial Grove approved. Revision to the BS in Business Administration approved. Chair Report. President Report. Online Instruction Policy – First Reading completed. Vice Chair Report. Chief Student Affairs Officer Report. Associated Students Report. APC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Staff Rep Report. Open Discussion on the consequences of the Election Results and Questions about the campus Structural Deficit. Good of the Order.